Comparative metabolic profiling of Cordia myxa leaves and fruits based on UPLC-ESI/MS-MS analysis and investigation of antioxidant activities and enzyme inhibitory properties - Heba A. S. El-Nashar; Gokhan Zengin; Abdalrahman Tarek; Omayma A. Eldahshan (Scientific Reports)
Abstract Cordia myxa, Assyrian plum, is an edible deciduous plant belonging to the family Boraginaceae and exhibited different traditional and pharmacological activities, including wound healing, emollient, expectorant, hepatoprotective, immune-modulator, and hypoglycemic. Our study aimed to investigate the metabolic profiling of C. myxa leaves and fruits growing in Egypt using the Ultra Performance Liquid Chromatography-Mass Spectrometry (UPLC-MSn) technique. Alongside, we determined its antioxidant properties and enzyme inhibitory activity against acetylcholinesterase (AChE), butyrylcholinesterase (BChE), tyrosinase, α-glucosidase, and α-amylase. UPLC-MSn analysis revealed the identification of 24 and 19 compounds in the leaf and fruit extracts, respectively. The identified compounds cover different phytochemical classes like phenolic acids, flavonoids, phenolic glycosides, lignans, anthocyanins and fatty acids, flavonoids being the predominant one. The leaf extract showed stronger antioxidant properties (DPPH: 100.80 mg TE/g; ABTS: 134.43 mg TE/g, CUPRAC: 290.87 mg TE/g; FRAP: 205.78 mg TE/g), compared to the fruit extract (DPPH: 22.45 mg TE/g; ABTS: 91.74 mg TE/g; CUPRAC: 41.39 mgTE/g; FRAP: 33.63 mg TE/g). In contrast to other antioxidant assays, the metal-chelating ability of the fruit extract (20.59 mg EDTAE/g) was greater than that of the leaf extract (9.94 mg EDTAE/g). The AChE inhibitory effect of fruit extract (2.59 mg GALAE/g) was higher than that of leaf extract (2.51 mg GALAE/g), but the leaf extract (1.68 mg GALAE/g) showed a stronger BChE inhibitory effect than the fruit extract (1.25 mg GALAE/g). Further, the fruit extract showed almost 2.5 times greater tyrosinase inhibitory activity than the leaf extract. The α-amylase and α-glucosidase inhibitory activities of the leaf extract were superior to those of the fruit extract. The molecular docking studies showed high docking affinities between three compounds, quercetin, kaempferol, and caffeic acid, with all targeted enzymes. As a conclusion, C. myxa signifies an excellent natural supply of treasured bioactive constituents with promising antioxidant and enzyme inhibitory effects. Further phytochemical studies should be performed to isolate the responsible compounds and investigate their mechanism of action.